Pengaruh Pengungkapan Other Comprehensive Income Terhadap Relevansi Nilai Informasi Akuntansi dengan Kualitas Audit sebagai Variabel Pemoderasi pada Perusahaan Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017 - Novita Sari, Via; Surya, Firman; Rosita, Irda (Jurusan Akuntansi Politeknik Negeri Padang, 2019)
This study aims to examine the effect of other comprehensive income disclosure towards value relevance of accounting information with the audit quality as moderating variables. The data used in this study is the secondary data obtained from the financial statements of consumer goods industry companies listed on the Indonesia Stock Exchange for the period of 2015-2017. The sampling technique used by using purposive sampling and it obtained the sample of 34 consumer goods industry companies. The data analysis technique used is multiple linear regression analysis and dummy variable moderation test (sub-group) using SPSS version 20. The results showed that the disclosure of other comprehensive income do not affect the value relevance of accounting information which is moderated by audit quality.